RELASI PANCASILA, AGAMA DAN KEBUDAYAAN: SEBUAH REFLEKSI - Saidi, Anas (Jurnal Masyarakat dan Budaya, 2009)
The relation between Pancasila and religions under sociological sphere creates a permanent tension. As a source of value and symbolical system, both factors has contested to gain followers and for defining reality, despite the fact that the two are actually in need and fulfill one another. Pancasila needs religion to enrich the meaning of life, and as the major source to deliver nation and statehood ethics based on social piousity derived from religion. This is also true that religion can become the source of answer on problems that lies beyond reality, such as the life after death explanation. On the other hand, religion needs Pancasila to gather universal values under different religions such as: justice, equality and humanity, which took different normative forms in each religion. Pancasila has the ability to mediate or bridge different primordial bounds derived from different religious cosmology, which could ignite conflict. This mutualistic symbiose can be achieved if both Pancasila and religion can realize their positions and limitations. In recent Indonesia, the relation between Pancasila and religion is under the most worrisome tension. At one point, the flow of religious (Islamic)-puritanism with its truth claim, and other claims, has changed the form of religiousity that was inclusive, tolerant, sincretic, adaptative; to another form that is exclusive, intolerant, anti-nationalism, anti-democracy, and anti-tradition. On the other point, the over-spirited voice of democracy radicalisation, gender equality and secularism claims has negated the need for ethics (religion) to enter the public sphere. To add the complication, the relation between Pancasila, religion, and culture, has to face globalization wave that disregard limits of tradition, nationalism and religious authority. Keywords: Pancasila, Agama, Kebudayaan.